2023
DOI: 10.3389/fendo.2022.1089918
|View full text |Cite
|
Sign up to set email alerts
|

Lactate-related metabolic reprogramming and immune regulation in colorectal cancer

Abstract: Changes in cellular metabolism involving fuel sources are well-known mechanisms of cancer cell differentiation in the context of carcinogenesis. Metabolic reprogramming is regulated by oncogenic signaling and transcriptional networks and has been identified as an essential component of malignant transformation. Hypoxic and acidified tumor microenvironment contributes mainly to the production of glycolytic products known as lactate. Mounting evidence suggests that lactate in the tumor microenvironment of colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 184 publications
0
3
0
Order By: Relevance
“…The malignant transformation of tumour cells promotes the evolution of metabolic pathways, 31 while abnormal metabolic molecules, such as lactate and adipokines, act as oncogenic pathway regulators. [32][33][34] CRC is a typical metabolism-related cancer, and diabetes is the most common metabolic disease asso- SFRP2 is a member of the Secreted Frizzled Related Protein family, whose well established function is to inhibit Wnt/β-catenin signalling pathway by binding to Frizzled receptors, inhibiting cell proliferation, migration, and invasion. 35 However, a growing number of studies have shown that SFRP2 is associated with metastasis, poor prognosis and treatment resistance in a variety of malignant diseases, including melanoma, prostate cancer and glioma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The malignant transformation of tumour cells promotes the evolution of metabolic pathways, 31 while abnormal metabolic molecules, such as lactate and adipokines, act as oncogenic pathway regulators. [32][33][34] CRC is a typical metabolism-related cancer, and diabetes is the most common metabolic disease asso- SFRP2 is a member of the Secreted Frizzled Related Protein family, whose well established function is to inhibit Wnt/β-catenin signalling pathway by binding to Frizzled receptors, inhibiting cell proliferation, migration, and invasion. 35 However, a growing number of studies have shown that SFRP2 is associated with metastasis, poor prognosis and treatment resistance in a variety of malignant diseases, including melanoma, prostate cancer and glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal metabolism is a hallmark of cancer, with special energy requirements and excessive proliferation of tumour cells being mutually reinforcing. The malignant transformation of tumour cells promotes the evolution of metabolic pathways, 31 while abnormal metabolic molecules, such as lactate and adipokines, act as oncogenic pathway regulators 32–34 . CRC is a typical metabolism‐related cancer, and diabetes is the most common metabolic disease associated with an increased risk (~40%) for CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation